1999
DOI: 10.1159/000018065
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Formulations of Cyclosporin A in the Treatment of Severe Atopic Dermatitis

Abstract: Background: Cyclosporin A (CsA) has been shown to be highly effective in the therapy of atopic dermatitis (AD). However, little information exists on the treatment of AD patients with Sandimmun Neoral® (Neoral), a microemulsion of CsA with improved pharmacokinetic properties in comparison to Sandimmun®. Objective: We have compared the efficacy and tolerability of Sandimmun and Neoral. Methods: In a randomised, monocentric, double-blind, cross-over pilot study (n = 14), each formulation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(69 citation statements)
references
References 9 publications
2
65
0
2
Order By: Relevance
“…The study comparing two different formulations of cyclosporin observed a more rapid response (after 2 weeks) in the group treated with the microemulsion (Neoral®) compared patients receiving the older formulation Sandimmun®. After 8 weeks of treatment, the mean decrease was similar in both groups 29 …”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…The study comparing two different formulations of cyclosporin observed a more rapid response (after 2 weeks) in the group treated with the microemulsion (Neoral®) compared patients receiving the older formulation Sandimmun®. After 8 weeks of treatment, the mean decrease was similar in both groups 29 …”
Section: Resultsmentioning
confidence: 67%
“…All 15 studies were performed in Europe. Sample size ranged from 10 to 106 patients with the majority (80%) of studies including less than 50 patients 23,25,27,29–37 . Three studies included only children, four studies both children and adults, and eight studies exclusively adults (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…While all formulations of CSA are effective in AD, the microemulsion formulation demonstrated more rapid onset of action and greater initial efficacy relative to the conventional formulation in one double-blind, cross-over study. 40 Modified microemulsion formulation of CSA is not bioequivalent to the non-modified formulation (both are available in oral capsules and solution), and the medications should not be used interchangeably.…”
Section: Cyclosporinementioning
confidence: 99%
“…Several studies have shown that oral cyclosporin A (CyA) is beneficial in the treatment of children with severe AD [22, 23, 24, 25]. CyA inhibits T cell activation and cytokine production [21, 22], thus potentially downregulating crucial steps in the immunopathogenesis of AD.…”
Section: Introductionmentioning
confidence: 99%